Human rights in the context of modern state - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the author reviews the problems of human rights and their implementation, impact of theConstitutional Court of Ukraine on the mechanism for protecting human rights. Author draws рarticular attention to the importance and role of the justice reforms to protect the constitutional human rights and citizens in Ukraine.